Child Marriage: Girls Marrying Too Young is a Human Rights Issue that Demands Global Attention - Andrew John Macnab (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2026)
All girls have the right to grow up free of gender-related violence and to be able to benefit from being educated. Investing in the education of girls is recognized to be one of the best investments a country can make because of the health, social, and economic benefits that accrue, not just for the educated young woman but for broader society. Problematically, child marriage is still commonplace globally, and in addition to being a human rights issue, girls being made to marry too young robs them of their childhood and also of the ability to benefit fully from their education. The negative effects of marrying too young can impact whole lifetimes; common consequences include pregnancy complications, the risk of spousal violence, and significant mental health issues. UNICEF and the WHO have called for action to reduce child marriage by providing adolescent girls with life skills training, comprehensive sexual health education, and support to stay in school, in addition to working at a community level to change attitudes that potentiate the cultural beliefs that potentiate the custom. As global health advocates, we need to recognize child marriage as a fundamental human rights issue that demands global attention, and look for ways to contribute to the support and empowerment of girls who are at risk.